2021
DOI: 10.1136/bjophthalmol-2020-317683
|View full text |Cite
|
Sign up to set email alerts
|

New digital models of care in ophthalmology, during and beyond the COVID-19 pandemic

Abstract: COVID-19 has led to massive disruptions in societal, economic and healthcare systems globally. While COVID-19 has sparked a surge and expansion of new digital business models in different industries, healthcare has been slower to adapt to digital solutions. The majority of ophthalmology clinical practices are still operating through a traditional model of ‘brick-and-mortar’ facilities and ‘face-to-face’ patient–physician interaction. In the current climate of COVID-19, there is a need to fuel implementation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…We flagged, for example, that the triadic hub-spoke model is somewhat labor intensive and unlikely to be scalable, whereas hub-home is limited by patients’ digital and material setup. Other models have also been described [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…We flagged, for example, that the triadic hub-spoke model is somewhat labor intensive and unlikely to be scalable, whereas hub-home is limited by patients’ digital and material setup. Other models have also been described [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…They can be applied to any field and pathology that needs further investigation on its mechanisms and treatment. In clinical practice, these integrative approaches will lead to new digital care models for human-centered ophthalmology including telemedicine, at-home monitoring, and AI-driven preventive and personalized care 67) .…”
Section: Discussionmentioning
confidence: 99%
“…Risk of transmission of COVID-19 is potentially high in outpatient ophthalmology practice because of close proximity, multiple tests and long visit duration [ 8 , 13 ]. A survey conducted in two tertiary eye centres in the USA revealed that fear of COVID-19 exposure was associated with a fourfold increase in the odds of loss to follow-up [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indian optometrists also shifted towards teleconsultations during the pandemic [ 25 ]. In Singapore, some eye care institutions have adopted a model where community optometrists are empowered to follow up with patients with eye diseases, thereby reducing patient traffic at tertiary eye centres [ 13 ]. Our study revealed that there were limited screenings done for Plaquenil toxicity, diabetic retinopathy and glaucoma in the Indian centre during the lockdown.…”
Section: Strategies For Future Pandemic Responsementioning
confidence: 99%